An investigation using wavelet analysis into velocity perturbations under the influence of elevated freestream turbulence at transition onset - Hernon, D; Walsh, E; McEligot, D (2006)
The development of streamwise-orientated disturbances at transition onset for zero-pressure gradient boundary layer flow under the influence of 1.3% freestream turbulence intensity is presented. The analysis concentrates on the development of turbulent spots and other coherent structures with the use of wavelet analysis. The turbulent spot structure is shown to change dramatically in shape, sign of perturbation velocity and energy content from the near wall region to the boundary layer edge. An increased number of turbulent structures are observed near the boundary layer edge, all with negative perturbation velocities, compared to those of positive perturbation velocity in the near wall region. The wavelet maps demonstrate some interesting features of turbulent spot development including regions of high frequency disturbance growth prior to the spot passing the sensor. Distributions of peak negative, peak positive and averaged perturbation velocities were obtained at three streamwise positions prior to transition onset. As transition onset approached the magnitude of the negative value far exceeded the positive and their relative positions within the boundary layer changed considerably. The results presented in this report give further insight into the physics of pre-transitional flow illustrating the influence of negative perturbation velocity in the transition process. Furthermore, the importance of peak instantaneous perturbations compared to averaged values is also demonstrated, a feature of the flow that computational techniques will have to model in order to accurately predict transition phenomena. Copyright © 2006 by ASME.